2019
DOI: 10.3390/molecules24081477
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Tumor-Targeting MRI Contrast Agent Based on Linear Polylysine Derivatives

Abstract: We developed a tumor-targeted contrast agent based on linear polylysine (PLL) by conjugating a small molecular imaging agent, fluorescent molecule and targeting agent amino phenylboronic acid onto the amino groups of polylysine, which can specifically target monosaccharide sialic acid residues overexpressing on the surface of tumor cell membranes. Further, 3,4,5,6-Tetrahydrophthalic anhydride (DCA) was attached to the free amino groups of the polylysine to change to a negative charge at physiology pH to lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The trueness of wide diverse boric acid application is confirmed by recent investigation of bacteria′s chemotaxis towards boric acid as a novel chemoattractant (Hida et al 2017). In the latest literature data, it is also confirmed that boric acid is the required component of tumour-targeting agent (Sun et al 2019). Its role, in the form of phenylboronic acid as a part of large molecule/agent, is the recognition of sialic acid residues on the malignant cancer cell surface.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The trueness of wide diverse boric acid application is confirmed by recent investigation of bacteria′s chemotaxis towards boric acid as a novel chemoattractant (Hida et al 2017). In the latest literature data, it is also confirmed that boric acid is the required component of tumour-targeting agent (Sun et al 2019). Its role, in the form of phenylboronic acid as a part of large molecule/agent, is the recognition of sialic acid residues on the malignant cancer cell surface.…”
Section: Introductionmentioning
confidence: 74%
“…Its role, in the form of phenylboronic acid as a part of large molecule/agent, is the recognition of sialic acid residues on the malignant cancer cell surface. Since sialic acid residues are not overexpressed in the normal cells, the proposed whole agent shows higher, selective cytotoxicity for malignant cells than for normal cells (Sun et al 2019). Recent dental clinical studies included estimation of subgingivally delivered 0.75% boric acid gel in chronic periodontitis (Kanoriya et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…has dramatically expanded the clinical scope of MRI technology. 2,3 At present, gadolinium (Gd) chelates are the most widely used MRI CAs in the clinic because the MRI images produced by T 1 -weighted CAs are brighter, are easier to be discerned by the naked eye and thus are preferred by physicians. [4][5][6][7] The first Gd chelates approved by the US Food and Drug Administration (FDA) (i.e., Magnevist s ) have been in clinical use for over 30 years.…”
Section: New Conceptsmentioning
confidence: 99%
“…CAs act as imaging probes that bind to the tissues/cells of interest and present them with greater conspicuousness on images, by altering how the signal or energy is exhibited by the pathology compared to surrounding healthy tissue [ 68 , 69 ]. While CAs can be used to improve image quality by enhancing the image contrast between pathological and normal tissues, they are not tumour-specific or pathology-specific and can exhibit non-specific biodistribution [ 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. In addition, conventional imaging techniques are only capable of detecting abnormal breast lesions, and thus are unable to provide further information and characteristics of the molecular profiles of BC which could improve clinical outcomes [ 13 ].…”
Section: Early Detection Is Criticalmentioning
confidence: 99%